2018
DOI: 10.1016/j.jad.2018.07.077
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the course of suicidal ideation response to ketamine

Abstract: Background: No pharmacological treatments exist for active suicidal ideation (SI), but the glutamatergic modulator ketamine elicits rapid changes in SI. We developed data-driven subgroups of SI trajectories after ketamine administration, then evaluated clinical, demographic, and neurobiological factors that might predict SI response to ketamine. Methods: Data were pooled from five clinical ketamine trials. Treatment-resistant inpatients (n = 128) with DSM-IV-TR-diagnosed major depressive disorder (MDD) or bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 36 publications
4
36
2
2
Order By: Relevance
“…10 Ballard et al found that 29% of depressed patients had no or minimal antisuicidal response to a low-dose ketamine (0.5 mg/kg) infusion, which is similar to our findings. 25 Interestingly, this study found no baseline sociodemographic or clinical characteristics that reliably distinguished antisuicidal responders and non-responders. The reasons for no differences in baseline sociodemographic and clinical characteristics between antisuicidal responders and nonresponders were unclear.…”
Section: The Main Findings Of This Single-arm Open-label Trialcontrasting
confidence: 53%
“…10 Ballard et al found that 29% of depressed patients had no or minimal antisuicidal response to a low-dose ketamine (0.5 mg/kg) infusion, which is similar to our findings. 25 Interestingly, this study found no baseline sociodemographic or clinical characteristics that reliably distinguished antisuicidal responders and non-responders. The reasons for no differences in baseline sociodemographic and clinical characteristics between antisuicidal responders and nonresponders were unclear.…”
Section: The Main Findings Of This Single-arm Open-label Trialcontrasting
confidence: 53%
“…Badania ostatnich lat wykazały również redukcję myśli i tendencji samobójczych po podaniu ketaminy, a efekt ten pojawiał się już po kilku godzinach od zakończenia wlewu i utrzymywał się nawet do 10 dni [13][14][15]. Należy jednakże podkreślić, że ketamina była mało skuteczna/nieskuteczna u pacjentów z bardzo nasilonymi i powracającymi myślami samobójczymi [13].…”
Section: Działanie Przeciwdepresyjne Ketaminyunclassified
“…Badania ostatnich lat wykazały również redukcję myśli i tendencji samobójczych po podaniu ketaminy, a efekt ten pojawiał się już po kilku godzinach od zakończenia wlewu i utrzymywał się nawet do 10 dni [13][14][15]. Należy jednakże podkreślić, że ketamina była mało skuteczna/nieskuteczna u pacjentów z bardzo nasilonymi i powracającymi myślami samobójczymi [13]. Kolejne badania kliniczne wskazują na szybkie przeciwdepresyjne działanie wlewów ketaminy nie tylko w przypadku dużej depresji opornej na klasyczną farmakoterapię [16][17][18] bądź terapię z zastosowaniem wstrząsów elektrycznych [19], ale również w chorobie afektywnej dwubiegunowej [12,17,[20][21][22], zespole obsesyjno-kompulsywnym [23] oraz chronicznej postaci zespołu stresu pourazowego [24].…”
Section: Działanie Przeciwdepresyjne Ketaminyunclassified
“…Ketamine treatment has been shown to result in rapid reductions in both SI and depressive symptoms in several clinical trials [ 11 13 ]. However, while ketamine is considered a promising treatment for patients with treatment-resistant depression and SI, individual patients vary in their response to ketamine [ 14 , 15 ], and some individuals do not respond sufficiently, even with serial, titrated treatments. The reasons for the heterogeneity of response to ketamine are unclear but may reflect differences in individuals’ underlying demographic attributes, pathophysiology, genetic makeup, and clinical features [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study the sociodemographic variables of positive family history of alcohol abuse disorder in a first-degree relative, higher BMI and negative history of suicide attempts were associated with improvements in depression scores post- ketamine infusion. Ballard, Yarrington [ 15 ] developed data-driven groups of SI trajectories after ketamine administration, pooled from five clinical ketamine trials. This study evaluated clinical, demographic and neurobiological factors that might predict SI response to ketamine and found that a longstanding history of chronic SI and self- injury were associated with non-response to ketamine.…”
Section: Introductionmentioning
confidence: 99%